Peripherally Inserted Central Line Catheters following Hand and Wrist Infections. Issue 11 (21st November 2022) - Park, Rachel H.; Stephens, Kristen L.; Forster, Grace L.; Freilich, Aaron M.; DeGeorge, Brent R.
Abstract : Background: Hand and wrist infections may cause varying degrees of morbidity requiring antibiotic therapy of variable duration and often operative intervention. Peripherally inserted central line catheters (PICCs) are placed when an extended course of intravenous antibiotics is anticipated. The present study aims to analyze utilization and impact of PICC placement on the management of hand, wrist, and forearm infections. Methods: The PearlDiver Patients Records Database was queried to identify patients who underwent treatment for infection of the hand, wrist, and forearm between 2010 and 2018. Logistic regression analysis was utilized to evaluate the association of patient-related risk factors with PICC utilization, complications, readmissions, and length of stay (LOS). Results: A total of 24, 665 patients with an upper extremity infection were included in the study. Ultimately, 416 patients required a PICC placement (1.69%). Patients with older age, male gender, certain medical comorbidities, and infection involving deeper structures were more likely to require a PICC. Ninety-day all-cause medical complication rates were significantly higher for the PICC group (19.7% versus 6.7%) compared to those without. Any hospital readmission rates were significantly higher for PICC group at 90 days (28.4% versus 6.3%) and 1 year (35.8% versus 10.9%). Readmission rates remained slightly higher at 1 year for both groups. The PICC group demonstrated significantly longer LOS by 2 days (7.72 days versus 5.14 days). Conclusion: While not required for the majority of hand, wrist, and forearm infections, PICC placement is associated with increased medical complications, more frequent hospital readmissions, and longer LOS.